Tinjauan Hukum Islam terhadap Pernikahan dengan Wali Hakim (Studi Kasus di KUA Kecamatan Bulo, Kabupaten Polman) - Mukran H. Usman; A. Hawariah; Rosmita, Rosmita; Nurfatimah Muh. Tahir (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to determine the cause of the marriage of guardian judges in the KUA, Bulo District, Polman Regency and to find out the review of Islamic law on this phenomenon. The research method used was field research with descriptive analysis techniques and applies a phenomenological and juridical-normative approach. The results showed that; 1) Among the factors in the occurrence of marriage with the guardian judge at the KUA, Bulo Sub-district, Polman Regency, is because there are no living lineage guardians and or no Muslim lineage guardians; 2) According to Islamic law, marriage with a guardian judge is legal if it has fulfilled the conditions and pillars that have been determined both in positive law and Islamic law, where the KUA Kecematan Bulo, Polman Regency stipulates that the guardian judge is a Muslim, akil, and balig.